Nightlife clusters of coronavirus disease in Tokyo between March and April 2020. (13th October 2020) - Takaya, S.; Tsuzuki, S.; Hayakawa, K.; Kawashima, A.; Okuhama, A.; Kanda, K.; Suzuki, T.; Akiyama, Y.; Miyazato, Y.; Ide, S.; Nakamura, K.; Nomoto, H.; et al.
Abstract: We analysed associations between exposure to nightlife businesses and severe acute respiratory syndrome coronavirus 2 PCR test results at a tertiary hospital in Tokyo between March and April 2020. A nightlife group was defined as those who had worked at or visited the businesses. We included 1517 individuals; 196 (12.9%) were categorised as the nightlife group. After propensity score matching, the proportion of positive PCR tests in the nightlife group was significantly higher than that in the non-nightlife group (nightlife, 63.8%; non-nightlife, 23.0%; P < 0.001). An inclusive approach to mitigate risks related to the businesses needs to be identified.